Pemberian Expected Approach Time (EAT) pada Pesawat Arrival Berdasarkan Average Time Interval (ATI) di Bandara Sultan Thaha Jambi - Bahrawi, Ahmad (Politeknik Penerbangan Makassar, 2021)
Thaha Airport approach clearance given for arrival aircraft does not contain information in the form of Expected Approach Time (EAT) which is the estimated time given by the Air Traffic Controller (ATC) to the arrival aircraft that is delayed to leave the holding fix which then continues the approach to landing. The condition caused the inefficiency of the aircraft maneuver because the pilot did not know the estimated time to approach. The provision of Expected Approach Time (EAT) to aircraft arrival can affect the smoothness and safety of flight traffic. In certain circumstances there is a communication failure of the aircraft arrival, then a pilot will follow the last EAT instructions given. As we know, the events of communication failure no one can know when it will happen and it is inevitable. A Controller can only reduce the risk of conflict from the occurrence of this by providing flight traffic services by providing EAT when the aircraft makes first contact. If given EAT, the pilot gets certainty so that it no longer asks the traffic position in front of him. Pilots can also adjust the speed of the aircraft thus reducing holding if it is required to hold. Therefore, EAT's provision of arrival aircraft affects the smoothness and safety of flight traffic.